Efektivitas Penerapan Model Project-Based Learning pada Mata Pelajaran Instalasi Penerangan Listrik - Desrika Zulfiyanti; Aswardi Aswardi (Jurnal Pendidikan Teknik Elektro, 2023)
This research was conducted to determine the effectiveness of students' learning process using the Project-Based Learning learning model in the Electrical Lighting Installation subject in class XI TKL SMK N 1 Bukittinggi. The learning process for Electrical Lighting Installation in class The Project-Based Learning learning model is a learning model that is suitable for use in learning Electrical Lighting Installation because it increases student activity, trains students to think critically, and develops students' skills. This research uses a type of experimental research in the form of a quasi-experiment with a non-equivalent control group design. The subjects in this research were class XI students at SMK N 1 Bukittinggi in the 2023/2024 academic year. The instrument used in this research used students' practical performance assessment sheets. The research results showed that the learning outcomes of students using the Project-Based Learning learning model were superior to the learning outcomes of students using conventional learning models. Therefore, learning using the Project-Based Learning learning model can be said to be effectively applied to the Electrical Lighting Installation subject.